Effect of Gender, Locale and School Types on the Academic Anxiety of Secondary School Students - Mohammad Hasan (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2022)
The extant study investigates the levels of academic anxiety across the gender, locale and school types and also explores whether gender, locale and school types obligate any effect on the academic anxiety of secondary school students. Data from secondary school students of Azamgarh District, Uttar Pradesh, India was collected by administering the Singh and Gupta’s Academic Anxiety Scale for Children (AASC) through simple random sampling technique. In view of measuring the effects of gender, locale and school types on academic anxiety, 2X2 factorial design was used.  The two way ANOVA along with t-test and descriptive statistical technique was performed. Results reveal that across all the selected demographic variables, considerable proportion of students was reported with high level of academic anxiety. The fetched results also confirm the effects of gender and school types on academic anxiety of school students. Present study implicates with many related studies wherein gender and school types reported to have significant effects on academic anxiety of the students.